2017
DOI: 10.1108/srj-09-2015-0135
|View full text |Cite
|
Sign up to set email alerts
|

How CSR and overall service quality lead to affective commitment: mediating role of company reputation

Abstract: Purpose The paper aims to focus on the relationships among corporate social responsibility (CSR), overall service quality (OSQ), company reputation and affective commitment. It investigates whether service quality or CSR is the primer driver of affective commitment. Also, the mediating role of company reputation was examined. Design/methodology/approach Structural equation modelling analysis provided support for the hypotheses from a sample of 522 retail banking consumers in Turkey. Findings Findings show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 88 publications
0
26
0
1
Order By: Relevance
“…The investigation thus answers the calls offered by past studies (e.g., [4,15,17,19]). The attitudinal and behavioral outcomes have also been invited in the past, e.g., [25]. Moreover, the relationship is proved both directly and indirectly (through serial mediation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation thus answers the calls offered by past studies (e.g., [4,15,17,19]). The attitudinal and behavioral outcomes have also been invited in the past, e.g., [25]. Moreover, the relationship is proved both directly and indirectly (through serial mediation).…”
Section: Discussionmentioning
confidence: 99%
“…The value of the current study could also be highlighted based on the numerous calls made by recent studies. For instance, Engizek and Yasin [25] highlighted that there is a need to investigate the attitudinal and behavioral customer outcomes of CSR and should be investigated in service sectors. Xie et al [17], while highlighting the antecedents of CCB, commented that there may exist some explanatory mechanisms that could bring a true picture and clarity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a company's good reputation communicates its reliability in all market transactions, resulting in increased commitment and loyalty (Bartikowski, Walsh, & Beatty, 2011). Several CSR studies, including that of Engizek and Yasin (2017), reveal that CSR directly influences the consumers' commitment to the company. For instance, have suggested that social responsibility has a direct effect on consumers' commitment.…”
Section: Commitment In Online Relationshipsmentioning
confidence: 99%
“…A consumer's positive perception of service quality could strengthen the overall company's associations, enhancing its image, competitive power, and profitability (Engizek & Yasin, ; Reichheld & Sasser, ; Shemwell, Yavas, & Bilgin, ; Yoon & Suh, ). The signalling theory (Spence, ) provides a rationale for the PSQ representing an aspect of corporate reputation building (Brammer & Pavelin, ; Gatti, Caruana, & Snehota, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous studies suggest that PSQ consists of two key aspects: overall service quality (OSQ) and specific service quality (SSQ; Brady, Joseph Cronin, & Brand, ; Engizek & Yasin, ; He & Li, ). Whereas the former refers to a consumer's overall long‐term accumulated perception of the gap between expectations and current service performance, the latter regards the major drivers of SQ—for example, tangibles, reliability, and responsiveness—that constitute the OSQ (Engizek & Yasin, ; He & Li, ). Among the two aspects of PSQ, OSQ has been identified by previous evidence as a closer antecedent of service quality outcomes compared with SSQ (Brady et al, ; He & Li, ; Tam, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%